Composite material for 430 stainless steel insulating slurry and preparation method thereof
By using composite materials of glass frit and inorganic filler, the 430 stainless steel insulating slurry has been solved to match the pressure resistance and thermal expansion coefficient of the 430 stainless steel insulating slurry, and an insulating layer with high pressure resistance and low warpage is achieved, ensuring the safety and durability of the product.
Patent Information
- Application Number
- CN202510232163.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-28
AI Technical Summary
The existing 430 stainless steel insulating slurry has poor pressure resistance, which can easily lead to warping, cracking and even falling off of the substrate, posing safety hazards, and the thermal expansion coefficient is not matched, affecting the durability of the product.
Using a composite material of glass frit and inorganic filler, a 430 stainless steel insulating slurry with excellent pressure resistance and matching thermal expansion coefficient is prepared by adjusting the raw material ratio and process flow. The specific steps include ball milling the glass frit and the inorganic filler in a ball mill and passing through the screen, and the resulting composite material has high pressure resistance and low warpage.
The 430 stainless steel insulating slurry has a voltage withstand value of more than 2500 V/80μm, and significantly reduces the warpage of the substrate, improves the density and electrical strength of the insulating layer, and ensures the safety and durability of the product.
Smart Images

Figure CN119724689A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thick film slurry insulation, and in particular to a composite material for 430 stainless steel insulation slurry and a preparation method thereof. Background Art
[0002] Thick film heaters use heating plates to convert electrical energy into thermal energy. Their characteristics include high power density and rapid heating. To ensure safe and efficient operation, the insulation layer required for this heater must have excellent high voltage resistance and electrical breakdown resistance. In addition, an insulation layer must be set between the thick film heater and the stainless steel. This insulation layer must not only have a similar thermal expansion coefficient to the substrate to ensure good fit and adhesion, but also be able to withstand multiple sintering processes without losing its performance.
[0003] With the advancement of technology, the shapes of thick film heaters are becoming increasingly diverse, such as special-shaped tubular designs. This requires that the insulating layer formed by the insulating medium slurry must have excellent anti-bending properties, otherwise it will directly affect the durability of the product. Especially in the field of new energy vehicles, thick film heaters are widely used for battery pack heating to meet the needs of use in cold environments. Due to the large size of thick film heaters in these applications, the 430 stainless steel insulation layer and the 430 substrate are required to have matching thermal expansion coefficients, otherwise the substrate is prone to warping, cracking or even falling off during use, and even leads to a decrease in pressure resistance, causing safety hazards such as leakage and fire.
[0004] Chinese patent CN101805125B discloses an insulating glass medium slurry for 430 stainless steel and a preparation method thereof. The raw materials for preparation include BaCO 3 30-80 copies; Al 2 O 3 : 0-10 parts; CaCO 3 :0-10 parts; SiO 2 : 40-50 copies; H 3 BO 3 : 0-5 parts; TiO 2 : 5-10 parts, although it solves the problem of mismatch between the thermal expansion coefficients of the insulating glass medium slurry and the metal substrate, its pressure resistance capacity still needs to be improved in actual use, and the substrate is prone to warping. Summary of the invention
[0005] In order to solve the problems in the prior art, the first aspect of the present invention provides a composite material for 430 stainless steel insulating slurry, the raw materials for preparing the composite material include glass frit and inorganic filler; in parts by weight, the raw materials for preparing the glass frit include: 50-90 parts BaSO 4 , 0-20 parts ZrO 2, 3-9 parts MgO, 2-5 parts CaO, 4-26 parts SiO 2 , 5-10 parts H 3 BO 3 , 0-5 parts TiO 2 , 0-2 parts K 2 CO 3 , 0-3 parts Li 2 CO 3 , 1-5 parts Al 2 O 3 .
[0006] In one embodiment, the raw materials for preparing the glass frit include, by weight: 60-90 parts BaSO 4 、5-18 parts ZrO 2 , 5-8 parts MgO, 2-3 parts CaO, 5-11 parts SiO 2 , 5-9 parts H 3 BO 3 , 2-4 parts TiO 2 , 0-2 parts K 2 CO 3 , 0-3 parts Li 2 CO 3 , 3-5 parts Al 2 O 3 .
[0007] In one embodiment, the mass ratio of the glass frit to the inorganic filler is (90-100):(0-10), excluding endpoint values.
[0008] In a preferred embodiment, the mass ratio of the glass frit to the inorganic filler is (90-95):(5-10), which may be 92:5, 92:8, 92:9, 95:5, 95:6, 95:8, 95:9.
[0009] In the present invention, SiO 2 , B 2 O 3 It is the basic material for glass formation. By adding BaO, MgO, CaO, TiO 2 、ZrO 2 , Li 2 CO 3 , Li 2 CO 3 、Al 2 O 3The frit is adjusted with materials such as glass frit and inorganic filler to obtain suitable melting temperature, sintering temperature and thermal expansion coefficient characteristics. At the same time, the inventors found that when the mass ratio of glass frit and inorganic filler in the system is (90-95): (5-10), the prepared composite material has strong pressure resistance and can significantly reduce warpage. This may be because within this mass ratio range, the inorganic filler can be evenly distributed in the middle of the glass frit, reducing the appearance of pinholes and bubbles in the insulating layer, and further improving the density and electrical strength of the insulating layer.
[0010] In one embodiment, the inorganic filler includes MgO, TiO 2 、ZrO 2 One or more of the MgO, TiO 2 、ZrO 2 All of them were analytical grade raw materials from Shanghai Myrel Chemical Technology Co., Ltd.
[0011] In one embodiment, the inorganic filler is ZrO 2 .
[0012] In one embodiment, the inorganic filler is TiO 2 and ZrO 2 .
[0013] In a preferred embodiment, the TiO 2 and ZrO 2 The mass ratio is 3:7.
[0014] In one embodiment, the MgO, TiO 2 The average particle size D50 is less than 10 μm.
[0015] In one embodiment, the ZrO 2 The average particle size D50 is less than 20 μm.
[0016] In one embodiment, the average particle size D50 of the composite material is 2-4 μm, and can be 2 μm, 3 μm, or 4 μm.
[0017] The second aspect of the present invention provides a method for preparing a composite material for 430 stainless steel insulating slurry, comprising at least the following steps: S1. Preparation of glass frit; S2. Ball-mill the glass frit and the inorganic filler in a ball mill for 5-6 hours and then pass through a sieve to obtain the product.
[0018] In one embodiment, the sieve is a 400 mesh sieve.
[0019] In one embodiment, the method for preparing the glass frit comprises: The raw materials for preparing the glass frit are placed in a mixer and mixed for 100-150 minutes, then placed in a crucible and heated to 1500-1800°C in a high-temperature furnace. After being melted evenly, poured into a water quenching pool for cooling, then taken out and drained, and dried at 100-120°C for 2-3 hours to obtain the obtained product.
[0020] In a preferred embodiment, the method for preparing the glass frit comprises: The raw materials for preparing the glass frit are placed in a mixer and mixed for 120 minutes. The materials are then placed in a crucible and heated to 1600°C in a high-temperature furnace. After being evenly melted, they are poured into a water quenching pool for cooling. The materials are then taken out and drained of moisture, and dried at 110°C for 2 hours.
[0021] Beneficial Effects 1. The present invention provides a composite material for 430 stainless steel insulating slurry and a preparation method thereof. The expansion coefficient of the glass powder for 430 stainless steel insulating slurry at this stage is relatively small. The present invention solves the safety hazards such as warping, cracking and even falling off of the substrate when sintering the insulating layer on a large substrate, and the relatively poor pressure resistance.
[0022] 2. The present invention first prepares a low-melting-point high-voltage resistant glass frit, then uniformly mixes the glass frit and an inorganic filler in a specific mass ratio, and crushes them to obtain a composite material for 430 stainless steel insulating slurry. The insulating slurry prepared by the composite material has a withstand voltage value of more than 2500 V / 80μm, and the warpage of the substrate is significantly reduced.
[0023] 3. The preparation method of the composite material for 430 stainless steel insulating slurry provided by the present invention has a simple preparation process and good market application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The following are actual pictures of the insulating slurries and electrodes prepared in the embodiments and comparative examples after sintering; in the pictures, 1# is comparative example 1, 2# is comparative example 2, 3# is comparative example 3, 4# is embodiment 1, 5# is embodiment 2, 6# is embodiment 3, 7# is embodiment 4, 8# is comparative example 4, 9# is comparative example 6, 10# is comparative example 5, 11# is embodiment 5, and 12# is embodiment 6.
[0025] Figure 2 The following are pictures of the insulating slurry prepared in Comparative Example 1 and Comparative Example 2 and the sintering thickness of the electrode after sintering; in the figure, a is Comparative Example 1 and b is Comparative Example 2.
[0026] Figure 3 The sintering thickness pictures of the insulating slurry and the electrode after sintering prepared in Comparative Example 3 and Example 1; in the figure, c is Comparative Example 3, and d is Example 1.
[0027] Figure 4 These are pictures of the insulating pastes prepared in Example 2 and Example 3 and the sintering thickness of the electrodes after sintering; in the picture, e is Example 2, and f is Example 3.
[0028] Figure 5 These are pictures of the insulating slurry prepared in Example 4 and Comparative Example 4 and the sintering thickness of the electrode after sintering; in the picture, g is Example 4 and h is Comparative Example 4.
[0029] Figure 6 This is a picture of the sintering thickness of the insulating slurry and the electrode after sintering prepared in Comparative Example 5 and Comparative Example 6; in the figure, i is Comparative Example 6 and j is Comparative Example 5.
[0030] Figure 7 The insulating pastes and electrodes prepared in Examples 5 and 6 are shown in Figure 1 and Figure 2 and their sintering thickness after sintering. In the figure, k is for Example 5 and l is for Example 6. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The experimental methods for which specific conditions are not specified in the examples are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be purchased commercially.
[0032] All raw materials in this invention were purchased from Shanghai Myril Biochemical Technology Co., Ltd.; among them, BaSO 4 , production number MKL-B802889; BaCO 3 , 99%, production number M18200; ZrO 2 , production number M90291; MgO, production number M85640; CaO, production number M04648; SiO 2 , production number MKL-S824278; H 3 BO 3 , production number M00259; TiO 2 , production number M05516; K 2 CO 3 , production number N08683; Li 2 CO 3 , production number M19611; Al 2 O 3 , production number M05516, production number M05398.
[0033] Example 1 In a first aspect of the present embodiment, a composite material for 430 stainless steel insulating slurry is provided, wherein the raw materials for preparing the composite material include glass frit and inorganic filler; in parts by weight, the raw materials for preparing the glass frit include: 76.27 parts BaSO 4 、18 parts ZrO 2 , 8 parts MgO, 3 parts CaO, 7.5 parts SiO 2 5.32 parts H 3 BO 3 , 4 parts TiO 2 , 5 parts Al 2 O 3 .
[0034] The mass ratio of the glass frit to the inorganic filler is 95:5.
[0035] The inorganic filler is ZrO 2 The ZrO 2 The average particle size D50 is 5 μm.
[0036] The average particle size D50 of the composite material is 4 μm.
[0037] A second aspect of the present embodiment provides a method for preparing a composite material for 430 stainless steel insulating slurry, comprising the following steps: S1. Preparation of glass frit: Place the raw materials for preparing glass frit in a mixer and mix for 120 minutes, then place the materials in a crucible and heat them to 1600°C in a high-temperature furnace. After melting evenly, pour them into a water quenching tank to cool, then take them out and drain the water from the materials, and dry them at 110°C for 2 hours to obtain the glass frit; S2. The glass frit and the inorganic filler are ball-milled in a ball mill for 5 hours and then passed through a 400-mesh sieve to obtain a product.
[0038] Example 2 In a first aspect of the present embodiment, a composite material for 430 stainless steel insulating slurry is provided, wherein the raw materials for preparing the composite material include glass frit and inorganic filler; in parts by weight, the raw materials for preparing the glass frit include: 76.27 parts BaSO 4 、18 parts ZrO 2 , 8 parts MgO, 3 parts CaO, 7.5 parts SiO 2 5.32 parts H 3 BO 3 , 4 parts TiO 2 , 5 parts Al 2 O 3 .
[0039] The mass ratio of the glass frit to the inorganic filler is 95:5.
[0040] The inorganic filler is TiO 2 and ZrO 2 The TiO 2 and ZrO 2 The mass ratio of ZrO is 3:7. 2 The average particle size D50 of TiO 2 The average particle size D50 is 2 μm.
[0041] The average particle size D50 of the composite material is 4 μm.
[0042] A second aspect of the present embodiment provides a method for preparing a composite material for 430 stainless steel insulating slurry, comprising the following steps: S1. Preparation of glass frit: Place the raw materials for preparing glass frit in a mixer and mix for 120 minutes, then place the materials in a crucible and heat them to 1600°C in a high-temperature furnace. After melting evenly, pour them into a water quenching tank to cool, then take them out and drain the water from the materials, and dry them at 110°C for 2 hours to obtain the glass frit; S2. The glass frit and the inorganic filler are ball-milled in a ball mill for 5 hours and then passed through a 400-mesh sieve to obtain a product.
[0043] Example 3 In a first aspect of the present embodiment, a composite material for 430 stainless steel insulating slurry is provided, wherein the raw materials for preparing the composite material include glass frit and inorganic filler; in parts by weight, the raw materials for preparing the glass frit include: 64.07 parts BaSO 4 、6 parts ZrO 2 , 5 parts MgO, 3 parts CaO, 11 parts SiO 2 5.32 parts H 3 BO 3 , 2.5 parts TiO 2 , 3 parts Al 2 O 3 , 1.43 copies K 2 CO 3 , 2.55 parts Li 2 CO 3 .
[0044] The mass ratio of the glass frit to the inorganic filler is 95:5.
[0045] The inorganic filler is ZrO 2 The ZrO 2 The average particle size D50 is 5 μm.
[0046] The average particle size D50 of the composite material is 4 μm.
[0047] A second aspect of the present embodiment provides a method for preparing a composite material for 430 stainless steel insulating slurry, comprising the following steps: S1. Preparation of glass frit: Place the raw materials for preparing glass frit in a mixer and mix for 120 minutes, then place the materials in a crucible and heat them to 1600°C in a high-temperature furnace. After melting evenly, pour them into a water quenching tank to cool, then take them out and drain the water from the materials, and dry them at 110°C for 2 hours to obtain the glass frit; S2. The glass frit and the inorganic filler are ball-milled in a ball mill for 5 hours and then passed through a 400-mesh sieve to obtain a product.
[0048] Example 4 In a first aspect of the present embodiment, a composite material for 430 stainless steel insulating slurry is provided, wherein the raw materials for preparing the composite material include glass frit and inorganic filler; in parts by weight, the raw materials for preparing the glass frit include: 64.07 parts BaSO 4 、6 parts ZrO 2 , 5 parts MgO, 3 parts CaO, 11 parts SiO 2 5.32 parts H 3 BO 3 , 2.5 parts TiO 2 , 3 parts Al 2 O 3 , 1.43 copies K 2 CO 3 , 2.55 parts Li 2 CO 3 .
[0049] The mass ratio of the glass frit to the inorganic filler is 95:5.
[0050] The inorganic filler is TiO 2 and ZrO 2 The TiO 2 and ZrO 2 The mass ratio is 3:7.
[0051] The ZrO 2 The average particle size D50 of TiO 2 The average particle size D50 is 2 μm.
[0052] The average particle size D50 of the composite material is 4 μm.
[0053] A second aspect of the present embodiment provides a method for preparing a composite material for 430 stainless steel insulating slurry, comprising the following steps: S1. Preparation of glass frit: Place the raw materials for preparing glass frit in a mixer and mix for 120 minutes, then place the materials in a crucible and heat them to 1600°C in a high-temperature furnace. After melting evenly, pour them into a water quenching tank to cool, then take them out and drain the water from the materials, and dry them at 110°C for 2 hours to obtain the glass frit; S2. The glass frit and the inorganic filler are ball-milled in a ball mill for 5 hours and then passed through a 400-mesh sieve to obtain a product.
[0054] Example 5 The specific implementation of this embodiment is the same as that of Embodiment 1, except that, by weight, the raw materials for preparing the glass frit include: 60 parts BaSO 4 , 5 parts ZrO 2 , 5 parts MgO, 2 parts CaO, 5 parts SiO 2 , 5 parts H 3 BO 3 , 2 parts TiO 2 , 3 parts Al 2 O 3 .
[0055] Example 6 The specific implementation of this embodiment is the same as that of Embodiment 1, except that, by weight, the raw materials for preparing the glass frit include: 90 parts BaSO 4 、18 parts ZrO 2 , 8 parts MgO, 3 parts CaO, 11 parts SiO 2 , 9 parts H 3 BO 3 , 4 parts TiO 2 , 5 parts Al 2 O 3 , 2 portions K 2 CO 3 , 3 parts Li 2 CO 3 .
[0056] Comparative Example 1 The specific implementation of this comparative example is the same as that of Example 1, except that the raw material for preparing the composite material for 430 stainless steel insulation slurry in this comparative example is only glass frit. The raw material for preparing the glass frit is the same as that of Example 1.
[0057] The second aspect of the present comparative example provides a method for preparing a composite material for 430 stainless steel insulating slurry, comprising the following steps: S1. Preparation of glass frit: Place the raw materials for preparing glass frit in a mixer and mix for 120 minutes, then place the materials in a crucible and heat them to 1600°C in a high-temperature furnace. After melting evenly, pour them into a water quenching tank to cool, then take them out and drain the water from the materials, and dry them at 110°C for 2 hours to obtain the glass frit; S2, ball-milling the glass frit in a ball mill for 5 hours and then passing it through a 400-mesh sieve to obtain a sintered glass frit.
[0058] Comparative Example 2 The specific implementation of this comparative example is the same as that of Example 3, except that the raw material for preparing the composite material for 430 stainless steel insulation paste in this comparative example is only glass frit. The raw material for preparing the glass frit is the same as that of Example 3.
[0059] The second aspect of the present comparative example provides a method for preparing a composite material for 430 stainless steel insulating slurry, comprising the following steps: S1. Preparation of glass frit: Place the raw materials for preparing glass frit in a mixer and mix for 120 minutes, then place the materials in a crucible and heat them to 1600°C in a high-temperature furnace. After melting evenly, pour them into a water quenching tank to cool, then take them out and drain the water from the materials, and dry them at 110°C for 2 hours to obtain the glass frit; S2, ball-milling the glass frit in a ball mill for 5 hours and then passing it through a 400-mesh sieve to obtain a sintered glass frit.
[0060] Comparative Example 3 The specific implementation of this comparative example is the same as that of comparative example 2, except that the raw materials for preparing the glass frit in this comparative example include: 85.42 parts BaSO 4 , 12.6 parts ZrO 2 , 5.6 parts MgO, 2 parts CaO, 5 parts SiO 2 , 8.88 parts H 3 BO 3 , 2.8 parts TiO 2 、3.5 parts Al 2 O 3 , 1.43 copies K 2 CO 3 , 2.55 parts Li 2 CO 3 .
[0061] Comparative Example 4 The specific implementation of this comparative example is the same as that of Example 1, except that the mass ratio of the glass frit to the inorganic filler is 80:20.
[0062] Comparative Example 5 The specific implementation of this comparative example is the same as that of Example 1, except that, by weight, the raw materials for preparing the glass frit are: 35 parts CaO, 32.5 parts SiO 2 , 16.7 parts H 3 BO 3 , 15.8 parts Al 2 O 3 .
[0063] Comparative Example 6 This comparative example was prepared using the specific implementation method of Example 1 in Chinese patent CN101805125B.
[0064] Figure 1 The following are actual pictures of the insulating slurries and electrodes prepared in the embodiments and comparative examples after sintering; in the pictures, 1# is comparative example 1, 2# is comparative example 2, 3# is comparative example 3, 4# is embodiment 1, 5# is embodiment 2, 6# is embodiment 3, 7# is embodiment 4, 8# is comparative example 4, 9# is comparative example 6, 10# is comparative example 5, 11# is embodiment 5, and 12# is embodiment 6.
[0065] Figure 2 The sintering thickness pictures of the insulating slurry and the electrode prepared in Comparative Example 1 and Comparative Example 2 after sintering; in the figure: a is Comparative Example 1, with a thickness of 110.74 μm; b is Comparative Example 2, with a thickness of 116.25 μm; Figure 3 The sintering thickness pictures of the insulating paste and the electrode prepared in Comparative Example 3 and Example 1 after sintering; in the figure: c is Comparative Example 3, with a thickness of 114.83 μm; d is Example 1, with a thickness of 115.16 μm; Figure 4 The sintering thickness pictures of the insulating paste and the electrode after sintering prepared in Example 2 and Example 3; in the figure: e is Example 2, with a thickness of 107.11 μm; f is Example 3, with a thickness of 113.2 μm; Figure 5 The sintering thickness pictures of the insulating paste and the electrode after sintering prepared in Example 4 and Comparative Example 4; in the figure: g is Example 4, with a thickness of 113.45 μm; h is Comparative Example 4, with a thickness of 113.08 μm; Figure 6 The sintering thickness pictures of the insulating slurries and electrodes prepared in Comparative Examples 5 and 6 after sintering; in the figure: i is Comparative Example 6, with a thickness of 107.57 μm; j is Comparative Example 5, with a thickness of 113.13 μm; Figure 7 The sintering thickness pictures of the insulating paste and the electrode after sintering prepared in Example 5 and Example 6; in the picture: k is Example 5, with a thickness of 112.6 μm; l is Example 6, with a thickness of 114.2 μm.
[0066] Performance Testing 1. Withstand voltage test: The composite materials for 430 stainless steel insulation slurry prepared in each embodiment and comparative example were mixed with the organic carrier in a mass ratio of 78:22 to prepare insulation slurry. The insulation slurry was printed on a 430 stainless steel substrate using a 150-mesh polyester screen, allowed to stand for 5 minutes, and the organic carrier was dried at 200°C. The organic carrier was sintered in an infrared sintering furnace at 850°C for 10 minutes, taken out, and cooled to room temperature. Figure 1 Repeat the above operation three times to make the sintering thickness reach more than 80μm (test its thickness as shown in Figure 2 As shown in the figure, the thickness is measured by a digital thickness gauge. Then, conductive silver paste is printed on the insulating layer. A withstand voltage tester is used to clamp the stainless steel substrate at one end and connect the conductive silver paste at the other end. The voltage at breakdown is the failure voltage. The withstand voltage parameters are: AC, 3KV, rise 10s, 5mA hold 2s.
[0067] Preparation method of organic carrier: add 38.8wt% of pineol and 33.3wt% of triethylene glycol monomethyl ether according to mass percentage into a beaker at 80°C and stir to form a uniform solution, then add 16.7wt% of rosin resin and 11.2wt% of ethyl cellulose resin while stirring, and after the resin is completely dissolved, continue stirring for 60 minutes, let it stand and cool to room temperature to obtain the product.
[0068] 2. Warpage The laser warpage measuring instrument was used to test each sample prepared for the above-mentioned withstand voltage test. The test results are shown in Table 1. In the table, the X plane and the Y plane represent the warpage test of the length and width of the sample in the horizontal direction, respectively.
[0069] Table 1
[0070] It can be seen from Table 1 that the insulating paste prepared by the composite materials of Examples 1-6 has a withstand voltage value of more than 2500 V / 80 μm, and the warpage of the substrate is significantly reduced; Comparative Example 5 does not contain BaCO 3 、ZrO 2 The withstand voltage value and the warping degree of the substrate are obviously insufficient for the raw materials; in Comparative Example 4, the amount of inorganic filler added is too much, and its failure voltage is too much reduced, which is only 1.48kV; After the insulating slurry and electrode sintering are prepared in Comparative Example 6, it is found that the warping of the substrate is too large, which is not suitable for application in larger thick film heaters.
Claims
1. A composite material for 430 stainless steel insulating slurry, characterized in that: The raw materials for preparing the glass frit include glass frit and inorganic filler; in parts by weight, the raw materials for preparing the glass frit include: 60-90 parts BaSO4, 5-18 parts ZrO2, 5-8 parts MgO, 2-3 parts CaO, 5-11 parts SiO2, 5-9 parts H3BO3, 2-4 parts TiO2, 0-2 parts K2CO3, 0-3 parts Li2CO3, 3-5 parts Al2O3; The mass ratio of the glass frit and the inorganic filler is (90-95): (5-10); The inorganic filler includes one or more of MgO, TiO2, and ZrO2.
2. The composite material for 430 stainless steel insulation paste according to claim 1, characterized in that: The average particle size D50 of the MgO and TiO2 is both less than 10 μm.
3. The composite material for 430 stainless steel insulation paste according to claim 1, characterized in that: The average particle size D50 of the ZrO2 is less than 20 μm.
4. The composite material for 430 stainless steel insulation slurry according to any one of claims 1 to 3, characterized in that: The average particle size D50 of the composite material is 2-4 μm.
5. A method for preparing the composite material for 430 stainless steel insulation slurry according to any one of claims 1 to 4, characterized in that: At least the following steps are included: S1. Preparation of glass frit; S2. Ball-mill the glass frit and the inorganic filler in a ball mill for 5-6 hours and then pass through a sieve to obtain the product.
6. The method for preparing the composite material for 430 stainless steel insulation slurry according to claim 5, characterized in that: The method for preparing the glass frit comprises: The raw materials for preparing the glass frit are placed in a mixer and mixed for 100-150 minutes, then transferred to a crucible and heated to 1500-1800°C in a high-temperature furnace. After being evenly melted, they are poured into a water quenching pool for cooling, then taken out and drained, and dried at 100-120°C for 2-3 hours to obtain the obtained product.
Citation Information
Patent Citations
High-thermal-expansion-coefficient thick-film dielectric paste for stainless steel base material and preparation method thereof
CN110880376A
Insulating medium paste and preparation method thereof, thick-film resistor and electronic product
CN116543952A
Insulating medium slurry based on stainless steel substrate and preparation method thereof
CN118692721A
Insulating glass composition
US5763339A
Lead-free low-melting-point glass paste for insulation coating
WO2011081022A1